P741 Fine-scale geographic distribution and ecological studies of Crohn's disease in France (2007–2014). (25th January 2019) - Genin, M; Fumery, M; Occelli, F; Savoye, G; Pariente, B; Dauchet, L; Vignal, C; Body-Malapel, M; Giovannelli, J; Sarter, H; Gower-Rousseau, C; Ficheur, G
Abstract: Background: A significant geographical variation in the incidence of Crohn's disease (CD) suggests the role of environmental factors in its pathogenesis. The objectives of this work were (i) to study the spatial distribution of CD cases in France from the database of the Programme de Médicalisation des Systèmes d'Information (PMSI), (ii) to study the factors associated with spatial heterogeneity and (iii) to identify clusters of high-prevalence. Methods: Patients with a CD diagnostic code were searched in the PMSI database between 2007 and 2014. To study the spatial distribution of prevalence for this period, a fine-scale spatial unit (5610 units at the national level) was used. The results were expressed as standardised prevalence ratio (SPR). An ecological regression measured the association between the risk of CD and spatial unit characteristics, such as access to the nearest reference centre, urbanisation and rurality, deprivation index (FDep index), latitude, and distance from polluting facilities. Elliptical spatial scan statistics were used to search high-prevalence clusters. Results: A total of 129089 patients with CD have been identified, with a national prevalence in 2014 of 203/100000 inhabitants. Significant spatial heterogeneity has been found (p ≤ 0.0001) (Figure 1). Ecological regression revealed a significant association between the risk of CD and the highest deprivation index (Relative Risk (RR) = 1.05[1.02–1.08]) and urbanisation (RR=1.08[1.05–1.15]). The spatial analysis detected 16 clusters with a CD relative risk ranging from 1.40[1.31–1.50] to 1.90[1.65–2.19]. Geographical distribution of age-and-gender Standardised Prevalence Ratios of Crohn's disease in France, 2007–2014. Conclusions: The French geographical distribution of CD is not uniformly distributed. Sixteen clusters with high-risk of CD have been identified. The poorest populations and industrialised areas were associated with a higher risk of developing CD.